A comparison of temperature distribution in PEMFC with single-phase water cooling and two-phase HFE-7100 cooling methods by numerical study. (19th July 2018) - Choi, Eun Jung; Park, Jin Young; Kim, Min Soo
Abstract: Thermal management has been considered as one of the critical issues in proton exchange membrane fuel cell (PEMFC). Key roles of thermal management system are maintaining optimal operating temperature of PEMFC and diminishing temperature difference over a single fuel cell and stack. Severe temperature difference causes degradation of performance and deterioration of durability, so understanding temperature distribution inside a single fuel cell and stack is crucial. In this paper, two-phase HFE-7100 cooling method is suggested for PEMFC thermal management and investigated regarding temperature change inside a fuel cell. Also, the results are compared to single-phase water cooling method. Numerical study of temperature distribution inside a single PEMFC is conducted under various conditions for the two different cooling methods. Fuel cell model considering mass transfer, electrochemical reaction and heat transfer is developed. The result indicates that two-phase HFE-7100 cooling method has an advantage in temperature maintenance and temperature uniformity than single-phase water cooling method, especially in high current density region. It is also revealed that the cell temperature is less dependent on system load change with two-phase cooling method. It indicates that the fuel cell system with two-phase cooling method has high thermal stability. In addition, the effect of coolant flow rate and coolant inlet pressure in two-phase HFE-7100 cooling method are discussed. As a result, two-phase cooling method showed reliable cooling performance even with low coolant flow rate and the system temperature increased as coolant pressure rose. Highlights: Two-phase HFE-7100 cooling method is suggested for PEMFC thermal management. Numerical study investigating temperature distribution inside PEMFC is conducted. Single-phase water cooling and two-phase HFE-7100 cooling methods are compared. Two-phase cooling shows better thermal performance than single-phase cooling.